Lesion-specific coronary artery calcium score to predict stent underexpansion - Yang, Wentao; Xu, Ke; Fu, Xi; Zhang, Weifeng; Hao, Ziyong; Sang, Zhenchi; Jiang, Lisheng; Qiu, Xingbiao; Tu, Shengxian; Shen, Linghong; He, Ben (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPrevious intracoronary imaging studies have shown that coronary artery calcium (CAC) is an independent risk factor of stent underexpansion; however, limited preintervention assessments of CAC have been performed using noninvasive methods. We aimed to determine the association between lesion-specific CAC score and stent underexpansion.MethodsIn this retrospective observational study, we included 416 lesions from 359 patients who underwent intravascular ultrasound (IVUS)-guided stent implantation. CAC of each lesion was quantified using the Agatston method derived from either nongated noncontrast chest CT (NCCT) or electrocardiogram-gated coronary CT angiography (CCTA). The primary endpoint was stent underexpansion defined as minimum stent area of <80% of the average reference lumen area.ResultsOverall, stent underexpansion occurred in 144 (34.6%) of 416 lesions. Lesion-specific CAC score was significantly negatively correlated with the stent expansion rate (in NCCT cohort, r = 0.8113, P < 0.05; in CCTA cohort, r = 0.8024, P < 0.05). The optimal cutoff values of lesion-specific CAC score to predict stent underexpansion were >200 in both NCCT (sensitivity, 91.4%; specificity, 66.8%) and CCTA (sensitivity, 84.6%; specificity, 64.3%) cohort, which were associated with 24.94-fold increased risk of stent underexpansion in NCCT cohort and 13.56-fold increased risk of stent underexpansion in CCTA cohort.ConclusionsIn this study, we found that lesion-specific CAC scores in both NCCT and CCTA cohorts were significantly independently associated with an increased risk of stent underexpansion, and the cutoff value to predict stent underexpansion was >200.